Using Information Systems to Sense Opportunities for Innovation: Integrating Postadoptive Use Behaviors with the Dynamic Managerial Capability Perspective. Issue 1 (2nd January 2016) - Roberts, Nicholas; Campbell, Damon E.; Vijayasarathy, Leo R.
Abstract: Fast-paced environmental changes require that managers quickly sense opportunities for organizational innovation. Information systems (IS) that support business intelligence and analytics help managers access and analyze data from various sources, thereby providing insight into potential opportunities. Building on the dynamic managerial capability perspective, we investigate the extent to which two managerial IS use behaviors—routine use and innovative use—influence a manager's volume and diversity of ideas for organizational innovation. We also examine the moderating role of three organization-level entrepreneurial orientation characteristics—autonomy, innovativeness, and risk taking. We test our research model with survey data collected from 248 managers. Our results show that routine IS use is not related to volume or diversity of ideas for organizational innovation. However, innovative IS use is positively related to idea volume and idea diversity. Furthermore, organizational autonomy and innovativeness positively moderate the aforementioned innovative use/idea relationships. Our study contributes to the literature by linking postadoptive IS use behaviors to managerial sensing ability, an important dynamic managerial capability. We also further the understanding of how organizational factors such as entrepreneurial orientation play a key role in determining whether, when, and how managers use IS to develop ideas for organizational innovation.